Mitigation of Edge Ringing for the Optimization of Highly Aberrated Coherent Optical Systems (Journal of Scientific Research, 2023)
The images of straight-edge objects formed by a coherent optical system with a circular aperture apodized with a shaded aperture have been studied. Image quality assessment parameters such as edge-ringing, edge-gradient, and edge-shift of the edge fringes have been investigated as a function of apodization parameters for various degrees of defocus, coma, and primary spherical aberrations. The reduction in the ringing pattern is more effective at the suitable combination of aberrations than the aberration-free cases and attains the minimum value for φd=2π where it is completely balanced with φd. It has been found that the image quality of straight-edge objects can be improved by combining specific aberrations with the appropriate apodizer.